KREATIVITAS GUGUM GUMBIRA DALAM PENCIPTAAN JAIPONGAN - Edy Mulyana (Pascasarjana Institut Seni Indonesia Surakarta, 2009)
The world of Sunda’s dance show on the decade of 1980th was startled by the appearance of Jaipongan. Its appearance became subject of story in various group of community from elite beurocrate, cultural experts and artists. The appearance of Jaipongan was not separated from the name of Gugum Gumbira, because this figure who has created it. This research aimed to reveal the matter of its creativity: Why did he create Jaipongan? How was the process in creating the Jaipongan and its socialization? Why does Jaipongan still exist up to now? Those were the questions which will be answered, while method which used is qualitative method with phenomenology approach. The result of the research showed that the birth of Jaipongan began from the desire of Gugum Gumbira for lifting people‘s art anymore, where at that moment its existence was marginalized. Its working concept started from female gender of the singer which called sinden or Ronggeng who had been attractive, except of that in realizing his creation start from people‘s character (vulgar, improvisators, and erotic). The existence of Jaipongan had great influence on tradition art of life, such as: Wayang Golek (puppet show), Degung, Kliningan, Calung, Topeng Banjet (Banjet Mask), Tarling ect, and even the pattern of strike and rhitmic pattern was mostly used by pop art, such as Dangdut, Jazz, Campur Sari and other pop art . In spreading of the work, there were supports from all media (printed and electronic) until Jaipongan became famous largely by the whole of element of the community, not only in local level but also in global level.Keywords: Jaipongan (Sundanese dance), creativity